THE ROLE OF THE POLICE REGARDING DIVERSION LEGAL MEASURES AGAINST CHILDREN AS CRIMINAL OFFENDERS TRAFFIC ACCIDENT (Research Study at Serdang Berdagai Police) - J.E. Melky Purba; M. Fikri Akbar; Jontario Lumban Gaol (Universitas Efarina, 2022)
Traffic accidents involving children result in the emergence of new problems in law enforcement in relation to determining sanctions for the child's responsibility. Through restorative justice, the basis for the solution is to achieve balance between the victim and the perpetrator of the crime, and then the criminal process can be carried out flexibly so that it is not limited to the need for justice. The goal of restorative justice is to restore the consequences of children's violations and efforts to improve children's morals so that children no longer repeat their actions. The aim of this research is to find out the role of the police in the process of legal action against children as perpetrators of traffic accident crimes based on the results of a research study at the Serdang Bedagai Police Station. By using a type of empirical research that is descriptive analysis, through data collection such as interviews, library data and document data sourced from primary legal materials and secondary legal materials which are then processed and analyzed. The role of the police in efforts to divert children as perpetrators of criminal traffic accidents at the Serdang Bedagai Police Traffic Unit is based on a report and investigators making a BAP, then Bapas conducting community research in the perpetrator's home environment, then Bapas issuing a letter of recommendation as to whether or not the diversion process is appropriate and The letter was handed over to investigators, investigators called the parties involved to carry out diversion